Preferential in vivo action of F15599, a novel 5-HT(1A) receptor agonist, at postsynaptic 5-HT(1A) receptors - Lladó-Pelfort, L (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: F15599, a novel 5-hydroxytryptamine (5-HT)(1A) receptor agonist with 1000-fold selectivity for 5-HT compared with other monoamine receptors, shows antidepressant and procognitive activity at very low doses in animal models. We examined the in vivo activity of F15599 at somatodendritic autoreceptors and postsynaptic 5-HT(1A) heteroreceptors. EXPERIMENTAL APPROACH: In vivo single unit and local field potential recordings and microdialysis in the rat. KEY RESULTS: F15599 increased the discharge rate of pyramidal neurones in medial prefrontal cortex (mPFC) from 0.2 µg·kg(−1) i.v and reduced that of dorsal raphe 5-hydroxytryptaminergic neurones at doses >10-fold higher (minimal effective dose 8.2 µg·kg(−1) i.v.). Both effects were reversed by the 5-HT(1A) antagonist (±)WAY100635. F15599 did not alter low frequency oscillations (∼1 Hz) in mPFC. In microdialysis studies, F15599 increased dopamine output in mPFC (an effect dependent on the activation of postsynaptic 5-HT(1A) receptors) with an ED(50) of 30 µg·kg(−1) i.p., whereas it reduced hippocampal 5-HT release (an effect dependent exclusively on 5-HT(1A) autoreceptor activation) with an ED(50) of 240 µg·kg(−1) i.p. Likewise, application of F15599 by reverse dialysis in mPFC increased dopamine output in a concentration-dependent manner. All neurochemical responses to F15599 were prevented by administration of (±)WAY100635. CONCLUSIONS AND IMPLICATIONS: These results indicate that systemic administration of F15599 preferentially activates postsynaptic 5-HT(1A) receptors in PFC rather than somatodendritic 5-HT(1A) autoreceptors. This regional selectivity distinguishes F15599 from previously developed 5-HT(1A) receptor agonists, which preferentially activate somatodendritic 5-HT(1A) autoreceptors, suggesting that F15599 may be particularly useful in the treatment of depression and of cognitive deficits in schizophrenia.